(untitled) (Publicaciones en Ciencias y Tecnología, 2007)
We propose a weak formulation of a heat conduction model for the detection of holes in metallic plates. An implicit discretization in time leads to a coupled, linear system of partial differential equations. At each time step, the system reduces to a Helmholtz problem with Robin boundary conditions and we show that its equivalent weak formulation is a well-posedness problem.